Evaluation of taper equations models for Pseudotsuga menziesii in the Argentina Patagonian Andes - Davel, M.; Trincado, G. (Forest Systems, 2000)
Different taper equations for Pseudotsuga menziesii (Mirb.) Franco plantations were evaluated in the Argentina Patagonian Andes. Functions fitted by Bruce et al. (1968), Real and Moore (1986), Kozak (1988) and Pérez et al. (1990) were tested. Data were collected from 268 trees scattered throughout 68 stands. The models were compared based on their bias and error when predicting volume, diameter and height. The validation was performed on a separate set of data. The best models were those developed by Kozak (1988) and Bruce et al. (1968).